In vivo detection of venous sinus distension due to intracranial hypotension in small animal using pulsed-laser-diode photoacoustic tomography - Rajendran, Praveenbalaji (2021)
Intracranial hypotension (IH) is a pathophysiological condition of reduced intracranial pressure caused by low cerebrospinal fluid (CSF) volume due to dural injuries from lumbar puncture, surgery, or trauma. Understanding the prognosis of IH in small animal models is important to gain insights on the complications associated with it such as orthostatic headache, cerebral venous thrombosis, coma, and so forth. Photoacoustic tomography (PAT) offers a novel and cost-effective way to perceive and detect IH in small animal models. In this study, a pulsed laser diode (PLD)-based PAT imaging system was used to examine the changes in the venous sinuses of the rat brain due to IH, induced through CSF extraction. After the CSF extraction, an increase in the sagittal sinus area by ~30% and width by 40% ± 5% was observed. These results provide supportive evidence that the PLD-PAT can be employed for detecting changes in sagittal sinus due to IH in rat model.